The micromagnetic study of stabilizing parameters for the interfacial skyrmions. (2023) - Sharma, Rajnandini; Mishra, Shrawan Kumar
Abstract: Skyrmions are localized topologically protected spin arrangements that can be mapped to a unit sphere. Various energy factors such as exchange energy, Dzyaloshinskii- Moriya (DM) interaction, uniaxial magnetocrystalline anisotropy, and Zeeman energy play a significant role in the stabilization of the skyrmions. Using micromagnetics as a tool, here we simulate these fundamental parameters required for stabilizing magnetic skyrmions. Our work comprehensively predicts how magnetic texture modification can be expected with variable values of the exchange constant, uniaxial magnetocrystalline anisotropy constant, DM constant, and saturation magnetization. Our results indicate that higher saturation magnetization dissolves the skyrmions. Among all these factors, DM interaction plays a crucial role, as the higher value of the DM constant helps in the evolution and creation of skyrmions. An optimum value of exchange energy is favorable for skyrmion stability. Similarly, a higher anisotropy constant further reduces the skyrmions size.